Genre Pedagogy: towards a more nuanced approach - Kristina Love (Universitas Negeri Padang, 2014)
The English portion of Indonesia’s Curriculum 2013 draws heavily on the Australian experience of syllabus and curriculum development, particularly in regard to a Genre Based Approach (GBA) to language and literacy (Emilia et al, In press). In its applications, this GBA has provided significant benefits in literacy education in L1 and ESL contexts in Australia, both in teacher preparation (eg Love, 2010) and school (eg Christie, 2012) contexts, and there is a strong likelihood that similar outcomes can be achieved for English Language Teaching (ELT) in Indonesia. However, there is a danger in both contexts that pedagogic practice in the academy and in school education will ‘fossilize’ around the formulaic teaching of prototypical genres, rather than being responsive to more nuanced understandings of generic structures and the patterning of language choices within these.Contributing to this danger is: the pressure of national literacy testing, which in Australia explicitly evaluates students’ performance in narrative and persuasion; the convenience for teachers of using codified ways of teaching genres in a time of increased demands on them; the infrastructure of the publishing industry which pre-packages resources for teachers’ convenience; and the internet or schools’ intranets, where ‘atomistic’, rather than cumulative strategies and resources are freely available.Furthermore, while there is a strong commitment at an academic level to communicative approaches to second language learning of English in both Australia and Indonesia, a challenge remains for L1 teachers in Australia, and possibly ELT teachers in Indonesia, to move beyond looking at language as simply a collection of rules and labels, even as they implement a GBA. Halliday's 1985 model of the relationship between context and the language system provides an important theoretical framework to return to as teachers continue to understand the subtleties involved in authentic and contextual language teaching and learning. A range of pedagogies have been developed in Australia using Hallidayan theory, including Humphrey’s 4x4 framework, which has been trialed in some ELT contexts in Indonesia (Emilia et al, In press). By providing a ‘word to text level’ model (Love & Humphrey, 2012), frameworks such as this offer teachers a means to shift their orientation from the continued use of the decontextualised grammar that many had grown up with, towards an orientation that unifies discrete and potentially fragmented aspects of grammar. Such approaches allow a more nuanced GBA that goes beyond the memorisation and application of rigid text type formulas, help teachers improve their meta-semiotic language and provide a strong groundwork for students as they learn to speak and write the more complex text types required in the senior years of schooling (Christie & Derewianka, 2008; Schleppegrell, 2004).In this presentation I will outline what some of these new orientations look like in the Australian context. I will then report on outcomes from a government funded project exploring teachers’ uptake of a Hallidayan oriented approach to the teaching of Persuasion, a text type that is currently the focus of the National Testing for Literacy. The design of our program with teaches drew on two key principles from Hallidayan linguistics: the principle of the metafunctions and the principle of stratification. I will focus on one teacher in this project as she shaped her pedagogy around these principles and supported her students to write engaging, as well as well-structured persuasive texts. Implications for a similarly more nuanced use of a GBA in an Indonesian ELT context could be explored following the presentation.